BASIS UNTUK SKEMA ASOSIASI GRUP MATRIKS ATAS Z3 - Nur Hamid; Cahyu Guswita; Saiful Islam; M. Faiz Nailun Ni'am (UNIVERSITAS NEGERI MALANG, 2021)
Some combinatorial problems in Mathematics can be studied via association scheme. By this scheme, algebra structure called Bose-Mesner algebra can be obtained. In this article, we show the explicit forms of the idempotent primitive of an association scheme for the group of order 48. Keywords: Association scheme, idempotent primitif